PENGARUH PENERAPAN PENDEKATAN SOMATIS, AUDITORI, VISUAL DAN INTELEKTUAL (SAVI) DENGAN TEKNIK KEPALA BERNOMOR TERSTRUKTUR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 11 PADANG - Fardian, Melko; Rahmi, Rahmi; Lovia, Lita (STKIP PGRI Sumbar, 2013)
Students comprehension of mathematical concepts is one of the factors that affect the learning outcomes of Mathematics. Students comprehension of mathematical concepts are still low in the SMPN 11 Padang seen from the results obtained studying Mathematics. The research aims to determine whether the students comprehension of mathematical concepts that apply SAVI approach with techniques Numbered Head of Structured better comprehension of mathematical concepts with conventional learning students at class VII SMPN 11 Padang. This type of research is experimental research, the design of randomized trials on the subject. The research instrument was a test of comprehension of mathematical concepts. Form of test used is a form of essays with a reliability test = 0.945. Based on hypothesis testing with MINITAB obtained P-value = 0.017, it can be concluded that the students comprehension of mathematical concepts that apply SAVI approach with techniques Numbered Head of Structured better comprehension of mathematical concepts with conventional teaching students in class VII SMPN 11 Padang with level 95 %.